Needs for Terengganu Sweet Melon growers for quality production using fertigation system - Mohd Nor, Zanariah; Abdullah, Intan Nur Mariam; Hamzah, Siti Raba’ah; Khandaker, Mohammad Moneruzzaman; Md Yusof, Nur Athiqah (Penerbit Universiti Sultan Zainal Abidin, 2022)
The Terengganu government needs 100 more fertigation growers of Terengganu Sweet Melon (MMT), to meet the European market demand. Undocumented local growers' needs for MMT fertigation farming hinder the local government’s efforts to retain and attract new local growers. Hence, this study’s objective was to explore the needs of MMT growers using the fertigation system for quality production in Terengganu. This qualitative study used semi-structured interviews complemented with Participatory Research Appraisal (PRA) tools for data collection. Through purposive sampling, 13 MMT growers volunteered as the study informants. The thematic analysis of the semi-structured interviews extracted six themes on growers’ needs. Almost all growers acknowledged MMT has promising prospects for its high market price and cost-effective fertigation system for quality production. However, they expressed six needs to help retain and support MMT fertigation technology adoption for quality production. All growers received a lack of technical consultancy; thus, their top urgent need was the advisory services on the technical knowledge and skills on MMT, fertigation system, and pests and diseases controls. Lack of financial support was also their urgent need for financial assistance to initiate, operate and maintain the high-cost infrastructure of the fertigation farming system. Different roles of agricultural-related and financial institutions were crucial to support their need for professional development, resources, and fertigation farm upscaling. In conclusion, MMT fertigation growers identified six needs that must be addressed for quality production. Their major needs were the technical advisory services on MMT and fertigation system, and financial assistance. Thus, the Terengganu government may incorporate the study findings to formulate an attractive policy for relevant government and NGOs’ roles to provide the relevant extension and advisory services, professional development packages, and friendly resources aid for the advancement of existing growers and to solicit new growers' participation.